Contribution of Esophagram to the Evaluation of Complicated Pediatric Eosinophilic Esophagitis. Issue 5 (November 2015) - Menard-Katcher, Calies; Swerdlow, Mathew P.; Mehta, Pooja; Furuta, Glenn T.; Fenton, Laura Z.
ABSTRACT: Objectives: In contrast to peptic strictures, clinically significant strictures in patients with eosinophilic esophagitis (EoE) may be subtle and go unrecognized at the time of endoscopy. We aimed to identify how often stricture was identified by endoscopy as compared with contrast esophagram. Methods: We retrospectively reviewed esophagram and endoscopy examinations of all of the patients with EoE with esophageal stricture seen at a tertiary care pediatric hospital over a 6-year period who had both procedures completed within a 3-month time frame. Medical charts were reviewed for clinicopathologic information including age, duration of symptoms, histology, and treatment. Results: Twenty-two children with EoE-associated stricture completed both esophagram and endoscopic assessments. Esophageal strictures were identified by esophagram, and not endoscopy, in 55% of these children. Patients with stricture identified at esophagram alone had a shorter duration of symptoms (2.1 years duration vs 5.4 years duration, P  = 0.03) than the group identified by endoscopy. Preoperative radiographic identification of a stricture was associated with dilation more often being performed. Conclusions: Esophagram is a valuable test to assess esophageal anatomy in children with complicated EoE. Esophagram may be able to detect subtle fibrostenosis earlier in the natural history of the disease than endoscopy.